'Every child that's born alive . . .' — Response to Regine Scholz and Earl Hopper. (March 2020) - Tubert-Oklander, Juan
This is my response to Regine Scholz's and Earl Hopper's commentaries on my 2019 Foulkes Lecture. Here I discuss Foulkes' concept of the matrix and the limits of his metaphor of individuals as knots in the communicational network, as well as the opposition and mutual relation between classical psychoanalysis and group analysis, on the one hand, and the relational perspective on the other. I also emphasize the urgent need to revise our underlying assumptions that contradict the discoveries of analysis, in order to develop a new interdisciplinary and all-inclusive paradigm of the human being.